THE PRICE OF POLITICAL SERVICES - Valdas Pruskus (Problemos)
In the article the price of political services as the expression of the value of political services is analysed. It coveres 5 dimensions, such as economical, social, political, psychological and financial. It is shown that a price of political services is complicated and because of this is not strictly definite, because in each case its components play different roles and are of different importance. A politician or political organization offering a political service (idea, project) to consumers (electors) also fix its price. The concrete actions to be carried out by a politician on the determination of the price of offered political service are discussed. Also factors affecting the increasse or reduce of prices of political services are discussed.